ISLAMIC ECO-HUMANISM IN EDUCATION: A STUDY OF TDBA AS A LOCAL MOVEMENT FOR GLOBAL TRANSFORMATION - Erawati, Dyah; Djabarudin, Maryam; Nuranisa, Vina; Darma, Surya Hadi; Mukti, Saepul (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study aims to analyze the integration of Islamic, humanitarian, and ecological values in the implementation of “Tatanén di Balé Atikan” (TdBA) at SMPN 2 Pasawahan, Purwakarta Regency, West Java Province, in addressing environmental crises and moral degradation. This program serves as a model of education based on local wisdom that fosters students’ spiritual, ecological, and social responsibility awareness. The research employs a qualitative phenomenological approach to explore the meaning of implementing Islamic Eco-Humanism values within the TdBA program at SMPN 2 Pasawahan. Data were collected through observation, interviews, and documentation involving the principal and implementing teachers. The data were analyzed inductively through reduction, presentation, and conclusion drawing. The implementation of TdBA at SMPN 2 Pasawahan reflects the principles of Islamic Eco-Humanism through the integration of tauhid (oneness of God), amanah (trustworthiness), and rahmatan lil ‘alamin (mercy for all creation) in ecological and spiritual learning. Activities such as planting, reflection, and communal work cultivate ecological and humanitarian awareness, making TdBA a model of local Islamic education that contributes to sustainable global transformation. The study concludes that the implementation of TdBA at SMPN 2 Pasawahan represents a tangible manifestation of Islamic Eco-Humanism, integrating the values of tauhid, amanah, and rahmatan lil ‘alamin into ecological and reflective learning. This program nurtures students’ spiritual, ecological, and humanitarian awareness while serving as a sustainable Islamic education model contributing to global transformation.